Планування контролю викидів, що забруднюють, енергетичних підприємств - Lyubimova, N. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2014)
The mathematical models of statistical decision making procedures where parameters of air pollution processes can be controlled are considered. Possibilities of one factor analysis of variance of the grouped realization of the controlled transient are shown when the last is represented by the probabilistic model of components of dispersions. Calculated correlations are obtained for planning of the grouped multiple measurements taking into account type I and type II control risks, that allow to maximize the probability of controlling the extreme emissions of pollutants. The experimental evaluation of parameters of plan of control the constituent smoke gases is conducted to verify the sensitivity of the model of components of dispersions to the short emissions. The proposed model of control, based on the use of analysis of variance of the grouped results of the measuring monitoring, can complement existing procedures of control of exceeding the pollution limits, promoting their sensitivity and reliability.